Treatment with BRAF/MEK: inhibitors in mutant BRAF V600E papillary craniopharyngioma - Eva Marie Erfurth; Peter Siesjö; Pia C Sundgren; Björn Hammar; Sara Kinhult (Endocrine Oncology)
Craniopharyngiomas (CPs) are rare brain epithelial tumours arising in the suprasellar region, infiltrating adjacent areas causing visual loss, panhypopituitarism, cognitive deficits and morbid obesity. Papillary CPs (PCPs) harbour in 94% BRAF mutation cases. Two patients with PCP and BRAF V600E mutations but with different tumour status were treated with BRAF and MEK inhibitors. Case I was diagnosed with biopsy and treated for 16 months with BRAF and MEK inhibitors. After 3.5 months, there was a 50% reduction of the tumour volume, and after 13 months, the tumour volume decreased from 2220 to 90 mm3 (96%). Two months after stopping the drugs, he was treated with fractionated cranial irradiation (54 Gy). No recurrence of the PCP was recorded. Eight months after stopping the drugs, he was diagnosed with an adenocarcinoma of the oesophagus, which led to his death 12 months later. In case II, a woman had had four surgeries due to recurrences of a PCP, and a BRAF V600E mutation was confirmed. After a new recurrence measuring 14 × 12 × 18 mm, she was started on BRAF and MEK inhibitors. After 4 months of treatment, a significant decrease to 8 × 9 × 13 mm was recorded. The treatment continued for 31 months, and the MRI demonstrated a stable unchanged size including scar tissue, with a volume reduction from 633 to 483 mm3. During treatment, her visual acuity improved in her left eye from 0.05 to 0.3. After stopping the drugs, ‘watchful waiting’ with repeated MRI was decided. She is now off treatment for 25 months, without any recurrence on MRI.